Efektivitas Project Based Learning Model Melalui Proyek PKA-KKA Dalam Pembelajaran Audit Internal di Diklat JFA Ahli Polri - Mustofa - Kamal (Jurnal Akuntansi, 2018)
This action research aims to assess the effectiveness of internal audit learning in the education and training of internal police of the National Police through project based learning models. The project was chosen with consideration; there is a gap between the conditions of 24 training participants from the role of law enforcement (watchdog) and new roles as candidates for internal auditors (assurance and consulting). The research method uses qualitative and quantitative.The project provided in the form of "making PKA and KKA" with the audit object is the police work unit in their respective regions. Learning effectiveness was assessed by trainers quantitatively, pre post test, and qualitatively, observations, and by training participants through online surveys. The results showed that there was an increase in understanding of internal audit through an increase in the average value of 36.46 from the average value of pre-test, 50.42 to the average post-test score, 86.88. While the results of the observations indicate that the internal audit learning process has been effective with evidence of the activities of PKA and KKA participants and projects that can be completed properly. On the other hand, a qualitative assessment of online participants showed that 58.3% of participants rated learning as having improved internal audit understanding. The rest assessed that interactive learning (25%) and fun (16.7%).Keywords: Internal Audit, Project Based Learning Model